Can we ensure safe schools?: a collaborative guide on focused strategies for school safety - Aefsky, Fern (Rowman & Littlefield, 2019)
"This book was written as a guide to practitioners, with input and strategies from police authorities, mental health professional and educators. School safety is an issue for school communities across the country. Collaboration with all stakeholders provide comprehensive strategies that can be applied to all schools and districts"--